PLOTINO, ARISTÓTELES Y EL ORIGEN DEL LIBRE ALBEDRÍO - ACOSTA LÓPEZ DE MESA, JULIANA (Disertaciones, 2012)
This article has as its main purpose to criticize the mainstream scholar tradition on the free will, according to which, there is no notion of free will in ancient Greek Philosophy. With this aim, I will make a direct critique to Michael Frede’s interpretation on the matter, who claims that this concept originates from the Stoic tradition, in some measure, because they are the first to develop an intellectual concept of the free will that, in his point of view, provides the best account on this issue. Moreover, I will show that Aristotle does have a notion of free will, in my opinion, even much more broad and effective than the merely intellectual one, for it explains, among other things, the possibility of choosing evil. Finally, in order to evaluate the limitations of the intellectualist free will, I shall use the analysis of the problem provided by Plotinus.
Keywords: Free will; Frede; Aristotle; Plotinus; Stoicism